(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article discusses the issues of developing creative and innovative thinking skills in young people through the process of analyzing works of visual art. It substantiates that examining the content, color palette, composition, and ideological direction of artworks is an important factor in developing independent and non-standard approaches to reality among youth. In addition, practical recommendations are provided on the use of interactive methods during lessons and on enhancing artistic perception.